Graceling: The Graphic Novel - Cashore, Kristin; Hinds, Gareth, 1971- (New York, NY : Etch, 2021)
"Katsa is a Graceling, one of the rare people born with an extreme skill. As niece of the king, she lived a life of privilege until the day her ability to kill a man with her bare hands revealed itself during a royal banquet. Now she acts as her uncle's enforcer, traveling the kingdom and threatening those who dare oppose him. But everything changes when she meets Po, a foreign prince Graced with combat skills who is searching for the truth about his grandfather's disappearance. When Katsa agrees to help him, she never expects to learn a new truth about her own Grace--or about a terrible secret that could destroy them all. With "gorgeous storytelling" ( School Library Journal, starred review) and characters "crafted with meticulous devotion" ( Kirkus Reviews, starred review), Graceling is a beloved classic that has continued to resonate with readers for over a decade."--Provided by publisher.
Keywords: Murder -- Comic books, strips, etc; Girls -- Comic books, strips, etc -- Conduct of life; Conduct of life -- Comic books, strips, etc; Fantasy -- Comic books, strips, etc; Kings and rulers -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Voyages and travels -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Young adult fiction; Murder -- Fiction; Girls -- Fiction -- Conduct of life; Conduct of life -- Fiction; Kings and rulers -- COmics; Friendship -- Fiction; Fantasy fiction; Graphic novels